Apathy in Parkinson's disease patients - M. R. Nodel (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2014)
pathy in Parkinson's disease (PD) patients is one of the least studied manifestations of a broad range of neuropsychic disorders. According to numerous researchers, the rate of apathy in PD patients is 17–80%. The structural and neurochemical changes associated with PD have been considered to be the leading pathophysiological factors of apathy. The possible general pathophysiological mechanisms are discussed for apathy and hypokinesia, depression, executive (frontal) cognitive functions, and sleep disorders in PD patients. The pathophysiological commonality of apathy, hypokinesia, and executive functions is probably based on bilateral disorders of functional links of the striatum and dorsolateral, medial parts of the prefrontal cortex. A combination of apathy and depression in PD patients may be due to dysfunction of the structures of the limbic system and medial orbital prefrontal cortex, which are responsible for the motivationally driven behavior. Variability of relationships of apathy with hypokinesia, depression, cognitive impairments, sleep disorders at different stages of PD may be associated with the phenomenological heterogeneity of apathy. Apathy reduces quality of life, makes a significant contribution to disturbances of both everyday and social adaptation of PD patients. A study of the possibility for apathy correction using dopaminergic therapy is rather promising. Twenty patients with PD (the middle stage according to the Hoehn and Yahr scale, 2.5) received pramipexole (1.5–3.0 mg/day) to correct motor disorders. A statistically significant positive trend in the time course of apathy, according to the overall assessment by the Starkstein apathy scale (AS), was noted after 4–6 weeks of the therapy. Based on the results, no statistically significant correlation was observed between the dynamics of the overall apathy score and the dynamics of motor symptoms of PD on the unified rating scale for PD assessment («Motor functions»). We believe that this fact demonstrates the independent effect of pramipexole therapy against motivational disorders.